A Validation of Ajzen’s Theory of Planned Behavior: Prescribing Behavior of Otolaryngologists during COVID 19 Pandemic in Pakistan - Dr. Saima Batool; Dr. Yasir Khan; Faiza Masood; Dr. Ayesha Sarfaraz (Journal of Business & Tourism, 2021)
The objective of this investigation was to uncover the magnitude of unethical promotion practices employed by pharmaceutical firms on Otolaryngologists and decide if the acknowledged gifts impacts their feelings with respect to gifts received. It intends to evaluate the perceptions/attitude of doctors towards gifts offered by pharmaceutical organizations, and impact of these gifts on prescribing behavior. The purpose is to explore whether attitude toward the behavior significantly affect intention; and whether subjective norm significantly affect intention and whether perceived behavioral control significantly affect intention. The study explores whether intention significantly affect prescribing behavior and whether perceived behavioral control directly significantly affect prescribing behavior. The “Theory of Planned Behavior” TPB allows such appraisal and is utilized for assessing anti-biotic use. After the preliminary analysis,the review was dispersed amongst doctors in an open private training medical clinic and facilities. 196 finished surveys were gotten out of 397 Otolaryngologists, (50.5% adjusted reaction rate). Utilizing multivariate examination, the general expectation toward endorsing antibiotic was not truly unsurprising (model R2 = .134). PBC (relative weight = .354) was the main noteworthy indicators. Our exploration structure can additionally be utilized by policymakers to plan and assess intercessions that may adjust the association between doctors and patients to enhance anti-biotic solutions among COVID 19 patients for various districts and age groups. This methodology gives a structure to create strategy experiences by different partner gatherings. It gives an apparatus to policymakers to research different mediation arrangements.